Writing About Reading. - Dietrich, Maíra; Hogeschool Gent KASK; SCH School of Arts; School of Arts Gent (Gent : [s.n.], 2018)
'Writing about Reading' is a text about the experience of reading, writing, and the universe of libraries. Based on personal experiences and references, the text builds a field of interests and observations divided in short sections that are accompanied by collages.
eindwerk